2018
DOI: 10.1016/j.jcde.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetohydrodynamic two-phase flow-induced vibrations in vertical heated upward flow

Abstract: In this paper, a mathematical model is presented to determine the effect of electro-magneto-hydro-dynamic forces on steady-state fluid-induced vibrations of vapor and liquid water flow in a heated vertical channel. The two-phase flow model used in this study includes continuity, non-homogeneous Navier-Stokes, non-equilibrium temperature balance with an approximation of spherical harmonics method (P-1 model) for thermal radiation at low-pressure condition close to saturation (1–2 bars). Governing equations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The recreation results demonstrated that the micromixing execution and response are performed by CFD method in the Microreactor [23] and four-way micromixers [24]. The effect of the magnetic force was investigated by Jamalabadi et al [25][26][27][28]. The study of [28] is useful for recent advances and pharmacology advancements in blood flow [29].…”
Section: Introductionmentioning
confidence: 98%
“…The recreation results demonstrated that the micromixing execution and response are performed by CFD method in the Microreactor [23] and four-way micromixers [24]. The effect of the magnetic force was investigated by Jamalabadi et al [25][26][27][28]. The study of [28] is useful for recent advances and pharmacology advancements in blood flow [29].…”
Section: Introductionmentioning
confidence: 98%
“…The force balance conditions of the two-liquid model for any stage (i refers to fluid or vapor) in Table 3 can be found in Collier and Thome [3]. Here, the inertial force term in the interfacial momentum exchange model has been combined into single expressions to avoid the use of regime maps [16][17][18]. The Lorentz term considers powers other than weight and trituration powers, for example, magneto-hydrodynamic power.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Recently, Jamalabadi [16][17][18] worked on the EMHD effects on a straight up flow in annular pipe in a two-phase flow regime. However, the effect of MHD and nanoparticles on subcooled vertical pipe flow has not been calculated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Condensation of a pure single steam bubble [9][10][11][12][13][14][15][16] and a mixture bubble [17,18] have been studied extensively. Several researchers computationally investigated the bubble nucleation, growth, departure, film-and flow boiling, and condensation [19][20][21]. The simulation performed [22] focused on bubble behaviors under low-and high-pressure, different bubble sizes, and different subcooled temperatures; and compared different velocities and bubble lives for a single bubble.…”
Section: Introductionmentioning
confidence: 99%